Peritonitis caused by Alcaligenes denitrificans subsp. xylosoxydans: case report and review of the literature. - Morrison, A J (1986)
We report the third human case of peritonitis caused by Alcaligenes denitrificans subsp. xylosoxydans and review the English literature regarding community-acquired and nonsocomial infection and colonization that results from this bacterium. The biochemical and genetic characteristics supporting the pathogenic potential of A. denitrificans subsp. xylosoxydans are reviewed, and the antimicrobial susceptibility profile of the organism is summarized.